The year of what if [large type] - Patrick, Phaedra (Thorndike Press large print dynamic drama., 2024)
"Carla Carter knows she's finally found the one. She and her fianč, Tom, met through a dating agency she founded, and she's confident that they will dispel an old family curse claiming Carter women are unlucky in love. For peace of mind, Carla's family insists she visit a fortune teller before she ties the know. Except the tarot reveals that the love of Carla's life is not Tom, but one of the men she briefly dated during her European gap year twenty-one years ago. Carla sets off across Europe to track down her exes from that unforgettable year, desperate to prove the fortune teller wrong. From Spain to Portugal, Italy to France, will one be her perfect match?" --